High-Capacity Anode Materials for All-Solid-State Lithium Batteries - Miyazaki, Reona (Frontiers in Energy Research, 2020)
This mini review article summarizes the recent progress of the all-solid-state lithium ion batteries (LIBs) with high-capacity anodes. Although the theoretical capacity of silicon (Si) is exceptionally high, the large volume change during cycling is a severe drawback for practical applications. The volume change of the active materials leads to mechanical degradation and electrical contact loss, resulting in a poor cycling performance. Recently, the number of reports about Si anodes in liquid electrolytes has significantly increased, leading to the better understanding of the electrochemical performances of Si. For the realization of the LIBs with a high capacity and safety, high-capacity alloy anodes are highly required to be used in all-solid-state batteries. However, at the present stage, research studies of high-capacity anodes with solid electrolytes are scarce compared to the vast amount of reports using liquid electrolyte. The selection of solid electrolytes is also a key factor for the stable performance of high-capacity anodes in the all-solid-state batteries, while previous studies on Si anodes have mainly focused on the fabrication of the hollow structured anodes for reducing their volume expansion. This review will provide some reports about the cycling properties of high-capacity anodes in the all-solid-state batteries and the solid electrolyte interface (SEI) formation at the anode interface of solid electrolytes. The potential of the high-capacity anodes for practical applications in all-solid-state batteries will be discussed.